Exploring the English Learning Process Using Video Podcasts - Anjani, Resti; Sis Nanda, Deri (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study investigates the use of video podcasts in the English learning process of Grade XII students at SMA Xaverius Bandar Lampung, focusing on students’ engagement, language skill development, and learning motivation. A qualitative descriptive research design was employed. Data were collected through classroom observations conducted over three meetings and a questionnaire administered to 35 students to explore their learning experiences and perceptions. The findings revealed that the use of video podcasts positively influenced students’ English skills, particularly listening, speaking, writing, and reading. Students demonstrated improved ability to comprehend spoken English, summarize content, and present information orally with increased confidence. Questionnaire results indicated that the majority of students perceived video podcasts as motivating, enjoyable, and effective in enhancing vocabulary mastery and pronunciation, although some students experienced difficulties related to unfamiliar vocabulary and speech speed. However, this study was limited to a single school context and relied on qualitative data, which may affect the generalizability of the findings. Overall, video podcasts provide meaningful learning experiences and serve as an effective learning medium to support a more interactive and student-centered English learning environment.